Effective Use of Performance Requirements and Investment Incentive - Boroo, Zuzaan (Mongolian Journal of International Affairs, 2013)
This paper reviewed a theoretical background rationalizing performance requirements, particularly employment and training requirements which are used by host countries in conjunction with investment incentives as a FDI policy means to achieve economic objectives. And it discusses main observations from the study and proposes some policy alternatives helpful for the government of Mongolia to benefit from FDI through performance requirements in conjunction with investment incentives. DOI: http://dx.doi.org/10.5564/mjia.v0i17.86 Mongolian Journal of International Affairs, No.17 2012: 97-108